A Child with Nephrotic Syndrome and Late Congenital Syphilis - Lilly Zulkarnain-Malaon; R.H. Sardjito Djojohadipringgo; I Wajan Giri; Moch. Soebagyo Singgih (Paediatrica Indonesiana, 1974)
Underneath is a report of a casewith nephrotic syndrome that mightbe due to congenital syphilis.